Implementasi Pajak Karbon (Carbon Tax) sebagai Instrumen Pengendalian Emisi Gas Rumah Kaca pada Sektor Industri Manufaktur di Indonesia (SDG 13) - Maharani Nurrizky Australis; Agvinda Restalina; Gerlavista Elena Zuafris; Muhammad Dzikri Asshidiq; Muhammad Adymas Hikal Fikri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The increasingly alarming impacts of climate change have urged many countries, including Indonesia, to introduce more concrete policy instruments to control greenhouse gas (GHG) emissions. The manufacturing industry sector is one of the largest emission contributors in Indonesia, yet efforts to control it remain far from optimal. This study examines carbon tax as an environment-based fiscal instrument within the framework of green economy and environmental law, focusing on the manufacturing industry sector in Indonesia and its relevance to the achievement of Sustainable Development Goal 13 (SDG 13) on climate action. The research employs a normative juridical method with conceptual and statutory approaches, conducted through a literature review of regulations, policy documents, and relevant academic sources. The findings reveal that although Indonesia has established a legal basis for carbon tax through Law Number 7 of 2021 on Tax Regulations Harmonization, its implementation remains inadequate due to a range of structural obstacles. These include the unpreparedness of emission measurement and reporting systems, concerns over industrial competitiveness, capacity disparities among business actors, and weak institutional coordination in policy enforcement. Such conditions give rise to the risk that carbon tax will function merely as a symbolic policy without meaningful impact on industrial behavioral change. On the other hand, when seriously designed and implemented, carbon tax has the potential to serve as a key driver of industrial transformation toward energy efficiency, renewable energy adoption, and low-carbon technological innovation in alignment with the polluter pays principle and the sustainability principle in environmental law. This study concludes that strengthening the implementation of carbon tax in the manufacturing industry sector requires more operationally refined regulations, adequate institutional capacity building, and stronger integration between environmental fiscal policy and Indonesia's commitments under the SDG 13 agenda and the Paris Agreement.